2022
DOI: 10.5114/pg.2022.116373
|View full text |Cite
|
Sign up to set email alerts
|

Which is the best choice for Helicobacter pylori eradication? Dual therapy or quadruple therapy?

Abstract: Introduction: Standard triple therapy used to be the first-line treatment for Helicobacter pylori (Hp) infection, but today it is a treatment regimen with a low eradication rate due to increasing resistance to the antibiotics included in the triple therapy.Aim: To compare the eradication rates of dual treatment regimens and quadruple treatment regimens.Material and methods: Patients over 18 years of age, who were indicated to undergo upper gastrointestinal system (GIS) endoscopy for any reason, had their upper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Finally, 5604 participants from14 RCTs were enrolled in this meta-analysis [ Figure 1 ]. Noteworthy, 3 studies[ 7 15 16 ] were not included because the patients were not treatment-naive while another study[ 8 ] was not included because the therapeutic regimen was unclear, and the results were not distinguished by ITT and PP analysis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, 5604 participants from14 RCTs were enrolled in this meta-analysis [ Figure 1 ]. Noteworthy, 3 studies[ 7 15 16 ] were not included because the patients were not treatment-naive while another study[ 8 ] was not included because the therapeutic regimen was unclear, and the results were not distinguished by ITT and PP analysis.…”
Section: Resultsmentioning
confidence: 99%
“…[ 7 ] concluded that HDDT could achieve a comparably higher eradication rate than BQT, while Bacaksız et al . [ 8 ] showed that HDDT embraced a low eradication rate compared with BQT. Therefore, we conducted a meta-analysis to evaluate the efficacy and safety of HDDT versus BQT in eradicating H. pylori .…”
Section: Introductionmentioning
confidence: 99%
“…However, they are ineffective in more than 20% of patients, mainly due to the increasing resistant strains of one or more antibiotics used in these therapies ( 10 ). According to Maastricht V consensus suggestion, bismuth-containing quadruple therapy was recommended as the first-line treatment in regions where the clarithromycin (CLR) resistance rate exceeded 15%–20% ( 11 ). However, the decline in the eradication rate of H. pylori was due to multiple factors, including increased antibiotic resistance rate, low patient compliance, high bacterial load ( 5 ), and genotype of cytochrome P450 proteins 2C19 (CYP2C19) gene ( 7 ).…”
Section: Introductionmentioning
confidence: 99%